Dissemination of the Impact of Overfishing and Mitigation Efforts Through the Development of Marine Protected Areas - Latuconsina, Husain (Agrikan Jurnal Agribisnis Perikanan, 2023)
One strategic step is the development of conservation areas. Dissemination activities regarding the impacts of overfishing and the importance of developing conservation areas to support the sustainability of fish biological resources need to be optimized in various formal and non-formal activities, including at universities. Dissemination activities through discussion activities to groups of students who are members of the Ichthyology Study Club, Biology Study Program, Faculty of Mathematics and Natural Sciences, Islamic University of Malang were held on 15 August 2020, attended by 30 participants and took place online. Data collection using questionnaires as a form of evaluation is divided into two stages, including: 1) pre-test questionnaire before material presentation and discussion, and 2) post-test questionnaire after material presentation and discussion. The results of the dissemination of the impact of overfishing and the importance of conservation areas to support the sustainability of fish biological resources obtained different perceptions between before and after providing discussion material from the results of the pre-test and post-test based on six key questions. However, there is a change in perception for the better regarding overfishing and its impacts as well as development of conservation strategies as mitigation efforts. These results indicate that there is still a need to optimize dissemination in curricular activities through the development of courses or teaching materials in relevant courses as part of a conservation strategy in an effort to support the preservation of fish biological resources for sustainable use.